Attenuation of Mycobacterium tuberculosis functionally disrupted in a fatty acyl-CoA synthetase gene fadD5 - Dunphy, Kathleen Y. (2010)
One key adaptation that Mycobacterium tuberculosis established to survive long term in vivo is a reliance on lipids as an energy source. M. tuberculosis H37Rv has 36 fadD genes annotated as putative fatty acyl-CoA synthetase genes, which encode enzymes that activate fatty acids for metabolism. One such gene, fadD5 (Rv0166), is located within the mce1 operon, a cluster of genes associated with M. tuberculosis persistence. We disrupted the putative fatty acid binding site of fadD5 in H37Rv M. tuberculosis. No significant differences were found in the growth of the mutant and wild-type strains in vitro in nutrient-rich broth or in activated RAW264.7 cells. However, the fadD5 mutant was diminished in growth in minimal medium containing mycolic acid, but not other long-chain fatty acids. C57BL/6 mice infected with the fadD5 mutant survived significantly longer than those infected with wild-type, and the mutant never attained the plateau phase of infection in the mouse lungs. The steady-state infection phase was maintained for up to 168 days at a level one to two logs less than that shown by wild-type. These observations raise a rather intriguing possibility that FadD5 may serve to recycle mycolic acids for the long-term survival of the tubercle bacilli.